POLITIK HUKUM (konsep Oligarki Dalam Pandangan Siyāsah Syar'iyah) - Miftahol Fajar Sodik (Jurnal Jendela Hukum, 2023)
Political oligarchy represents a political system controlled by minorities in a country. Participation in the exploitation of the government of small groups often results in justice, arbitrariness that has political ownership rights of the small community, who have them as the bourgeoisie in the status of national and state life. The view of siyasah syar'iya which is derived from the principles of the Koran and hadith explains that the existence of apolitical system must be directed towards religious maintenance and social harmonization, therefore the existence of the government is burdened as a mandate for the welfare of society without differences in social status. As for one of the practices of nationalism without social differences taught by the Prophet Muhammad, it can be seen from the context of the Medina Charter as a constitution and a joint commitment between Muslims and non Muslims to live as a state with a common goal of being able to live in prosperity both socially, economically and political. As for the problems in this article, namely those related to Jeffrey A. Winters' views regarding political oligarchy and how the views of siyasah syar'iyah criticize it, this research is a library research which is descriptive analysis in nature.